2021
DOI: 10.1021/acs.jpcc.0c10511
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Carrier Dynamics of Amorphous Zinc Tin Oxide Graded Thin Films

Abstract: We report the fabrication of amorphous zinc tin oxide (ZTO) thin films using rf magnetron sputtering and rapid postannealing. A vertically graded composition alloy (Zn 1−x Sn x O) is constructed in a single amorphous layer, which exhibits strong visible light absorption. The ultrafast carrier dynamics of the ternary zinc tin oxide film is investigated by femtosecond transient absorption (TA) spectroscopy, which shows that the photocarriers in ZTO films have nearly identical relaxation dynamics under an ultravi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…The fast and slow decay components could be attributed to the defect trapping and inter-band carrier recombination in β-GaS thin films, respectively. These results are analogous to that reported for other semiconductor materials (Fang et al, 2016;Li et al, 2017;Kong et al, 2018;Yan et al, 2020;Li et al, 2021).…”
Section: Femtosecond Ta Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The fast and slow decay components could be attributed to the defect trapping and inter-band carrier recombination in β-GaS thin films, respectively. These results are analogous to that reported for other semiconductor materials (Fang et al, 2016;Li et al, 2017;Kong et al, 2018;Yan et al, 2020;Li et al, 2021).…”
Section: Femtosecond Ta Resultssupporting
confidence: 90%
“…The time resolution of the TA measurement system was ∼280 fs. Details of our TA measurement can be found in the previous report (Li et al, 2021).…”
Section: Femtosecond Ta Measurementmentioning
confidence: 99%
“…Details of our TA measurement can be found in a previous report. 23 The TA data also show that the strong PIA signal quickly vanish after one picosecond after zero delay time. The large width and fast decay of PIA signal agree with previous studies on the ND-TPA effect in semiconductors.…”
Section: Methodsmentioning
confidence: 83%
“…The time resolution of the TA measurement system was ∼280 fs. The experimental setup of femtosecond TA system is detailed further elsewhere …”
Section: Methodsmentioning
confidence: 99%
“…For instance, previous studies show that the ternary CuSnI films exhibit excellent hole mobility and improved performances compared to pristine CuI films. A detailed understanding of the carrier dynamics in semiconductors is crucial for both fundamental development and device engineering. In the past decade, considerable efforts have been devoted to revealing the carrier dynamics in semiconductors via time-resolved spectroscopies. Samu et al found that the recombination of excitons in CuI films is strongly dependent on the applied electrochemical bias, which is related to the populating/depopulating of trap states within the bandgap . Thus, doping of CuI with appropriate dopants should lead to drastic improvements in carrier mobilities and lifetimes.…”
mentioning
confidence: 99%